The causes of dispersal and the cost of carry‐over effects for an endangered bird in a dynamic wetland landscape. (17th May 2017) - Robertson, Ellen P.; Fletcher, Robert J.; Austin, James D.
Summary: The decision to disperse or remain philopatric between breeding seasons has important implications for both ecology and evolution, including the potential for carry‐over effects, where an individual's previous history affects its current performance. Carry‐over effects are increasingly documented although underlying mechanisms remain unclear. Here we test for potential carry‐over effects and their mechanisms by uniting hypotheses for the causes and consequences of habitat selection and dispersal across space and time. We linked hypotheses regarding different types of factors and information (environmental conditions, personal and public information) predicted to impact reproductive success and dispersal for an endangered, wetland‐dependent bird, the snail kite ( Rostrhamus sociabilis plumbeus ). To do so, we coupled structural equation modelling with 20 years of mark–recapture and nesting data across the breeding range of this species to isolate potential direct and indirect effects of these factors. We found that water depth at nest sites explained subsequent emigration rates via an indirect path through the use of personal, not public, information. Importantly, we found that these dispersers tended to initiate nests later the following breeding season. This pattern explained a phenological mismatch of nesting with hydrological conditions, whereby immigrants tended to nest later, late nesters tended to experience lower water depths, higher nest failure occurred at lower water depths and higher nest failure explained subsequent breeding dispersal. These results identified a novel potential mechanism for carry‐over effects: a phenological mismatch with environmental conditions (water depth) that occurred potentially due to time costs of dispersal. Our results also highlighted a substantial benefit of philopatry – earlier initiation of reproduction – which allows philopatric individuals to better coincide with environmental conditions that are beneficial for successful reproduction. These results have implications for our mechanistic understanding and prediction of carryover effects, and emphasize that local conservation strategies, such as water management, can explain future demography at distant sites connected through dispersal. Abstract : Understanding the causes and consequences of dispersal remains a challenge for wild populations. The authors identify critical linkages between habitat conditions across landscapes, where conditions in one location can impact current emigration and future reproduction at distant locations linked through dispersal in an endangered bird, the snail kite.